Characterization of Feruloyl Esterases Produced by the Four Lactobacillus Species: L. amylovorus, L. acidophilus, L. farciminis and L. fermentum, Isolated from Ensiled Corn Stover - Xu, Zhenshang; He, Huiying; Zhang, Susu; Guo, Tingting; Kong, Jian (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) play important roles in silage fermentation, which depends on the production of sufficient organic acids to inhibit the growth of undesirable microorganisms. However, LAB are not able to degrade cellulose and hemicellulose. Bacteria and fibrolytic enzymes are usually used as inoculants to improve the silage quality and digestibility. In the present study, we isolated four Lactobacillus strains (L. amylovorus CGMCC 11056, L. acidophilus CCTCC AB2010208, L. farciminis CCTCC AB2016237 and L. fermentum CCTCC AB2010204) with feruloyl esterase (FAE) activities from ensiled corn stover (CS) by a plate screening assay. The genes encoding FAEs were cloned and hetero-expressed in Escherichia coli. The optimal temperature and pH of these purified enzymes ranged from 45 to 50ºC and from 7.0 to 8.0, respectively. They could hydrolyze hydroxycinnamoyl esters in a substrate-specific manner when methyl ferulate, methyl caffeate, methyl ρ-coumarate and methyl sinapinate were used as substrates. Moreover, these four FAEs were able to hydrolyze CS to release hydroxycinnamic acids. Furthermore, these strains could degrade hydroxycinnamic esters, and L. amylovorus CGMCC 11056 was the most efficient strain among these four isolates. These results provided a new target for the development of inoculants to improve silage quality and digestibility.